Implementation of Shared Services in Multinational Corporations : Insights into challenges and successes - Makhneva, Olga (My University, 2018)
In recent years, a large number of multinational corporations have been implementing shared services aiming to streamline business processes, reduce costs and improve efficiency. In order to ensure successful transition to shared services, it is important to understand how the implementation process is done and what has the most significant influence on the outcomes. The main objective of this research is to investigate how to facilitate successful implementation of shared services, providing insights into challenges and successes of the large multinational corporations operating in the industrial engineering sector. The main research question of this study is divided into two questions, namely ‘What facilitates successful implementation of shared services?’ and ‘How is the implementation of shared services done by the companies within the industrial engineering sector?’. These questions are answered through discovering the most critical success factors, the process and the phases of the implementation and the most common challenges that companies encounter during implementation. This study adapts the qualitative research approach, enabling the researcher to profoundly explore the phenomenon and expand the current understanding of the shared services. The case study method has been selected for this research and the representatives of four case companies have been interviewed. The interviews were conducted with eight managers, who have been leading or participating in transition to shared services, based on the predefined open-ended questions which facilitated insightful discussion on the topic. The empirical data states that support and sponsorship of senior management is crucial to succeed in the implementation of such complex initiatives. It was also concluded that sufficient and suitable transition resources are vital to ensure fast-paced transition and high-quality deliverables. And most importantly, the findings of this research emphasise the importance of the focus on the end-to-end processes and the end user in order to maximise process efficiency, and thereby, better leverage benefits of the shared services business model, and ensure proper utilisation of new services. Thus, this study provides important managerial implications, enabling leaders to increase probability of successful implementation of shared services, as well as offers suggestions for future academic research.
Keywords: shared services, global business services, shared services centre